WOMEN'S LEADERSHIP MANAGEMENT IN GENDER PERSPECTIVE IN LAMPUNG PROVINCE UNIVERSITIES - Hadiati, Eti; Kamil, Badrul; Dwiyanto, Agus; Setianingrum, Diah Ayu; Setiyo, Setiyo (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
Gender inequality and injustice in an organization or company, educational institutions included, can still be found. The cause of these differences often occurs due to the influence of gender bias which is still commonly found in reference books, where women are positioned as